Duchenne muscular dystrophy in Saudi Arabia: a review of the current literature - Aldharee, Hitham (Frontiers in Neurology, 2024)
In the past three decades, significant improvements have occurred in the study of Duchenne muscular dystrophy (DMD). DMD is a rare, severe neuromuscular disease that causes death due to cardiovascular and respiratory complications among affected boys. Since the 1980s, ongoing preclinical and clinical studies have been conducted to explore the disease in depth and discover potential therapeutic strategies. In Saudi Arabia, it is unclear whether health services and research efforts are keeping pace with global achievements. Therefore, this review aims to explore the diagnostic and management strategies and research efforts in Saudi Arabia over the past three decades. I searched the PubMed/Medline, Scopus, and Web of Science databases and included all published articles on the epidemiology, genetics, diagnosis, and management of DMD/BMD in this review. The findings suggest a lack of local standardized diagnostic strategies, a poor understanding of epidemiology and common pathogenic variants, and a critical need for preclinical and clinical research. At the time of writing, no such comprehensive review has been published. Challenges, limitations, and future perspectives are also discussed in this article.